2011
DOI: 10.1177/1471082x1001100403
|View full text |Cite
|
Sign up to set email alerts
|

A bivariate INAR(1) process with application

Abstract: The study of time series models for count data has become a topic of special interest during the last years. However, while research on univariate time series for counts now flourishes, the literature on multivariate time series models for count data is notably more limited. In the present paper, a bivariate integer-valued autoregressive process of order 1 (BINAR(1)) is introduced. Emphasis is placed on models with bivariate Poisson and bivariate negative binomial innovations. We discuss properties of the BINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 19 publications
1
89
0
Order By: Relevance
“…Moreover, in accordance to the BINAR(1) process, dependence between any two series that comprise the MINAR(1) process is introduced by allowing for dependence between the respective innovation terms. Thus, if , it can be shown that Similarities with the corresponding properties of the BINAR(1) model (Pedeli and Karlis, 2011a) are apparent.…”
Section: The Multivariate Inar(1) Processmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, in accordance to the BINAR(1) process, dependence between any two series that comprise the MINAR(1) process is introduced by allowing for dependence between the respective innovation terms. Thus, if , it can be shown that Similarities with the corresponding properties of the BINAR(1) model (Pedeli and Karlis, 2011a) are apparent.…”
Section: The Multivariate Inar(1) Processmentioning
confidence: 86%
“…This study focus on the definition and study of appropriate models for multivariate count series. The proposed MINAR(1) model is a generalization of the BINAR(1) model (Pedeli and Karlis, 2011a) to the multi–dimensional space. Thus, it can be regarded as a useful tool for modelling more than two time series of correlated count data simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is usually very difficult to obtain the likelihood of higher-order INAR process, then WE procedure can be a good choice for the parameter estimation. Furthermore, the bivariate INAR process has been studied in the integer-valued time series literature (Pedeli and Karlis, 2011;Ristić, et al, 2012), then our proposed estimation and test idea can also be applied to these bivariate integer-valued time series processes.…”
Section: Discussionmentioning
confidence: 99%
“…This family is a generalization of the BINAR model of Pedeli and Karlis (2011) [15]. Likelihood-based estimators for model parameters were derived and their asymptotic properties obtained and prediction was also addressed.…”
Section: Discussionmentioning
confidence: 99%